Development of E-Learning for Speaking Skills Course with Local Wisdom of Papua - Hafid, Abdul; Firman; Agusta Mayor, Enjelita; Elly, Ridwan (JTP - Jurnal Teknologi Pendidikan, 2025)
Students must have speaking skills because they are very important for social interaction and work. This research aims to develop e-learning for the speaking skills course incorporating local Papuan wisdom. The type of research is development research. The concept of local wisdom applied specifically to learning materials includes social values and norms, traditional knowledge, customs, language, folklore, and culture. The research subjects involved 48 students from the Indonesian Language Education Study Program. This research was conducted at UNIMUDA Sorong. The research design uses the 4D (Four-D) model. The validity test was conducted by two validators and then analyzed using Aiken's V formula. The practicality test was conducted using student responses and then analyzed using Riduwan's formula. Effectiveness was tested using a t-test with normality and homogeneity tests as prerequisites. Based on the results of the research and discussion on e-learning for the speaking skills course with local Papuan wisdom, it is declared valid with an average score of 0.89 (very high validity). It is declared practical with an average score of 91.87 (very practical category). Effectively improves students' speaking skills based on the results of the t-test with a significance value of 0.000 (Sig. (2-tailed) data). This is less than the predetermined significance level of 0.05. The limitation of this research is that it only focuses on speaking skills. Only exploring Papua's local wisdom. Still unable to reach areas without internet access. This research contributes to the literature on speaking learning media that is responsive to local wisdom, particularly in the context of Papua. Supporting the theory that integrating technology and local wisdom can enhance language learning. The e-learning product produced is valid, practical, and effective, and can serve as a model for developing other language skills devices. Preserving local wisdom thru formal education.